Structural Priming and Frequency Effects Interact in Chinese Sentence Comprehension - Wei, Hang; Dong, Yanping; Boland, Julie E.; Yuan, Fang (Frontiers in Psychology, 2016)
Previous research in several European languages has shown that the language processing system is sensitive to both structural frequency and structural priming effects. However, it is currently not clear whether these two types of effects interact during online sentence comprehension, especially for languages that do not have morphological markings. To explore this issue, the present study investigated the possible interplay between structural priming and frequency effects for sentences containing the Chinese ambiguous construction V NP1 de NP2 in a self-paced reading experiment. The sentences were disambiguated to either the more frequent/preferred NP structure or the less frequent VP structure. Each target sentence was preceded by a prime sentence of three possible types: NP primes, VP primes, and neutral primes. When the ambiguous construction V NP1 de NP2 was disambiguated to the dispreferred VP structure, participants experienced more processing difficulty following an NP prime relative to following a VP prime or a neutral baseline. When the ambiguity was resolved to the preferred NP structure, prime type had no effect. These results suggest that structural priming in comprehension is modulated by the baseline frequency of alternative structures, with the less frequent structure being more subject to structural priming effects. These results are discussed in the context of the error-based, implicit learning account of structural priming.